Perceptions of Inequality - Markus Knell; Helmut Stix (Oesterreichische Nationalbank (OeNB), 2017)
Although people's perception of (income or wealth) inequality has important e_ects on their decisions as economic agents or voters, little is known about how perceptions relate to measured inequality. We present a novel formal framework that is based on the assumption that people typically do not observe the entire income (wealth) distribution and that their guesses about the extent of inequality are based on reference groups. This framework predicts that perceptions of inequality will change along positions in the income distribution and that for a speci_c position various dimensions of inequality perception are related to each other. First, low (high) income individuals overestimate (underestimate) their own position. Second, subjective estimates of average earnings increase with the own income position. Third, high or low income people have di_erent perceptions about the shape" of society (e.g. pyramid or diamond). Fourth, the subjective perception of inequality is lower for high-income individuals. Survey data from 40 countries provide strong support for the framework
Keywords: D31; D63; D83; C81; 330; Income distribution; perception of inequality; reference groups